2013
DOI: 10.3109/08880018.2013.771389
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Invasive Surgery for Adrenocortical Carcinoma in Children: Is It Safe?

Abstract: Laparoscopy in adrenocortical carcinoma is controversial due to high risk of local recurrence in case of per-operative spillage. We wanted to report the case of a successful laparoscopic transperitoneal adrenalectomy performed in a 3-year-old girl presenting a 5.5-cm adrenocortical carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…13 14 However, there are also reports of successful MIS in ACTs. 8 15 16 These reports are supported by the current German AWMF recommendations that advocate that a MIS approach in ACTs is feasible as long as the principles of oncological surgery are maintained. 17 Furthermore, a recent publication of adult ACT cases found evidence that the open and laparoscopic approach may be comparable in terms of recurrence-free survival for patients with stage I and II ACT when the principles of surgical oncology are respected.…”
Section: Discussionmentioning
confidence: 70%
“…13 14 However, there are also reports of successful MIS in ACTs. 8 15 16 These reports are supported by the current German AWMF recommendations that advocate that a MIS approach in ACTs is feasible as long as the principles of oncological surgery are maintained. 17 Furthermore, a recent publication of adult ACT cases found evidence that the open and laparoscopic approach may be comparable in terms of recurrence-free survival for patients with stage I and II ACT when the principles of surgical oncology are respected.…”
Section: Discussionmentioning
confidence: 70%
“…As these tumors are usually large and their capsules are friable, rupture and spillage frequently occurs. Few pediatric cases operated by endosurgery for small tumors (<55 mm) have been reported 34 . However, because of the overall aggressive nature, and the fact that upfront complete (R0) resection is the only chance of survival, the authors generally recommend against using MIS for preoperatively identified ACTs.…”
Section: Current Status Of Pediatric Oncologic Endosurgerymentioning
confidence: 99%
“…15 Few pediatric cases operated by laparoscopic approach for tumors smaller than 55 mm have been reported, with one conversion but no spill out and a good outcome. 17,31 Other Etiologies Rare etiologies of pathologic adrenal gland have been exceptionally reported in laparoscopic series such as adrenal teratoma and adrenal location of a metastatic rhabdomyosarcoma. 17 Despite the big size of the tumor, up to 8.5 cm long, laparoscopic removal was successful without recurrence.…”
Section: Adrenocortical Adenomamentioning
confidence: 99%